(untitled) (Contemporary Journal of Social Science Review, 2025)
This article critically examines the deviations in plot and characterization between Khaak aur Khoon, the historical novel by Naseem Hijazi, and its film adaptation. The study explores how the film alters key events, introduces new scenes, and modifies character portrayals, often emphasizing communal tensions and political ideologies more explicitly than the novel. While the novel intricately captures the social fabric of pre-Partition India, portraying interfaith relationships, village life, and the gradual rise of political consciousness, the film leans towards dramatization, reshaping key historical moments and omitting crucial narrative nuances. Furthermore, the article analyzes how the depiction of Partition-era violence, migration, and ideological struggles differs between the two mediums, influencing audience perception of historical events. The study highlights the challenges of adapting historical fiction into cinema, examining how creative liberties impact historical authenticity, emotional depth, and narrative fidelity. By comparing the novel and its film adaptation, this article provides insight into the artistic and ideological considerations involved in transforming historical narratives into visual storytelling.